2021
DOI: 10.3390/ijerph18083862
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Patient Needs Regarding Adverse Drug Reaction Reporting Smartphone Applications: A Qualitative Insight from Saudi Arabia

Abstract: Background: A pragmatic shift in the healthcare sector characterized by moving from curative to preventive approaches highlights the role of pharmacovigilance in patient safety. There have been few published studies on patient reporting of adverse drug reactions (ADRs) in Saudi Arabia. This qualitative study aims to explore the community opinions and the need for patient-friendly smartphone applications (SPAs) to enhance their participation in ADR reporting. Methods: Purposeful sampling was followed to recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
0
16
1
Order By: Relevance
“…72.4% of the present study's sample was aware of the SFDA-Spontaneous ADR reporting forms. These findings differ from those reported by Kassem et al who reported that 60% of their sample was unaware of SFDA-Spontaneous ADR reporting forms ( Kassem et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 99%
“…72.4% of the present study's sample was aware of the SFDA-Spontaneous ADR reporting forms. These findings differ from those reported by Kassem et al who reported that 60% of their sample was unaware of SFDA-Spontaneous ADR reporting forms ( Kassem et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 99%
“…83,84 10 | TECHNOLOGICAL ADVANCES AND DIGITAL PHARMACOVIGILANCE SYSTEMS Patient self-reporting may be easier to implement in regions with higher mobile phone penetration. In Saudi Arabia, Kassem et al 85 found that many patients were already aware of ADRs either through personal or family experience, and wanted more information and education on these. 85 In China, an evaluation of spontaneous ADR reports from children (made by the child or their carer) were found to comprise only 2.5% of 3348 reports.…”
Section: Engagement and Empowerment Of Communities In Pharmacovigilancementioning
confidence: 99%
“…In Saudi Arabia, Kassem et al 85 found that many patients were already aware of ADRs either through personal or family experience, and wanted more information and education on these. 85 In China, an evaluation of spontaneous ADR reports from children (made by the child or their carer) were found to comprise only 2.5% of 3348 reports. 86 Whilst access to the internet and ownership of a smartphone Drug Administration and Control and are then contacted by phone.…”
Section: Engagement and Empowerment Of Communities In Pharmacovigilancementioning
confidence: 99%
“…Studies were published between 2008 and 2021, and were conducted in a range of countries; Saudi Arabia (n = 3) [ 49 , 55 , 57 ], United Kingdom (n = 4) [ 44 , 58 , 63 , 64 ], USA (n = 2) [ 52 , 53 ], Ghana (n = 3) [ 29 , 48 , 66 ] with remaining studies from South Korea [ 33 ], Netherlands [ 50 , 62 ], Thailand [ 47 ], Canada [ 49 ], and Australia [ 14 , 45 , 59 ]. Detailed study characteristics are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%